Application of DNA Array Technology for Diagnostic Microbiology - Stephanie A Booth; Michael A Drebot; Graham A Tipples; Lai King Ng (Canadian Journal of Infectious Diseases)
Microarrays or DNA chips have been hailed as the ultimate experimental tool for research, drug discovery and diagnostics. They have the potential to perform a multitude of molecular tests simultaneously and to produce a wealth of information from a single clinical sample. Applications include genotyping, expression analysis and sequencing (1-4). The aim of this review is to provide a brief summary of current microarray technology and highlight the many ways in which it is being developed for use in clinical microbiology laboratories.